2016
DOI: 10.21451/1984-3143-ar724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coconut (Cocos nucifera) water with or without egg-yolk on viability of cryopreserved buck spermatozoa

Abstract: The effects of semen extenders containing coconut (Cocos nucifera) water alone or combined with egg yolk on viability of spermatozoa during cryopreservation of semen obtained from West African Dwarf (WAD) bucks were studied. Coconut water (5, 10, 15 and 20 ml/100 ml) was diluted with pooled semen samples in study I, while in study II, the pooled semen samples were diluted with egg yolk and coconut water (EYCW) at 5:10, 10:10 and 10:5 in Tris-based extenders. The control consisted of Tris-based extenders plus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Moreover, postchilled abnormal sperm count was consistently higher at all the concentrations of egg yolk (5-20%) with onion (EY5+O, EY10+O, EY20+O) followed by Aloe vera (EY5+A, EY10+A, EY20+A) at both 24 and 48 h of storage in present experiment, while the abnormalities were lowest without any additive (EY5, EY10, EY20) groups. Similarly, higher abnormal sperm percentage after Aloe vera treatment in West African Dwarf bucks (Olugbenga et al, 2011), and the non-significant difference between different groups (Daramola et al, 2016a) has been documented, while contradictory findings were reported in other studies (Khalifa and Abdel-Hafez, 2013;Daramola et al, 2016b). Non-significantly higher sperm abnormalities were observed in EY0 than EY5, EY10 and EY20 groups in the present study.…”
Section: Resultscontrasting
confidence: 66%
“…Moreover, postchilled abnormal sperm count was consistently higher at all the concentrations of egg yolk (5-20%) with onion (EY5+O, EY10+O, EY20+O) followed by Aloe vera (EY5+A, EY10+A, EY20+A) at both 24 and 48 h of storage in present experiment, while the abnormalities were lowest without any additive (EY5, EY10, EY20) groups. Similarly, higher abnormal sperm percentage after Aloe vera treatment in West African Dwarf bucks (Olugbenga et al, 2011), and the non-significant difference between different groups (Daramola et al, 2016a) has been documented, while contradictory findings were reported in other studies (Khalifa and Abdel-Hafez, 2013;Daramola et al, 2016b). Non-significantly higher sperm abnormalities were observed in EY0 than EY5, EY10 and EY20 groups in the present study.…”
Section: Resultscontrasting
confidence: 66%
“…Fructose is added to the diluent because the sperm plasma contains a variety of specific organic compounds, one of which is fructose. Egg yolk is a good diluent because it is affordable and accessible, has good energy source, and contains nearly the same physical and biochemical elements as sperm [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having water, sugars, proteins, salts, and vitamins in its composition, coconut water is easy to prepare and has a low cost (Carvalho et al, 2006;Rondon et al, 2008). Moreover, improvements in sperm cells integrity and viability in small ruminants have already been reported with the use coconut water (Cavalcante et al, 2014;Daramola et al, 2016;Brito et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…In seminal plasma, sperms have a limited survival time, thus the necessity of using diluents and cryoprotectants that can maintain sperm quality during the execution of preservation techniques and storage at low temperatures, providing an adequate environment for survival of these gametes and, consequently prolonging sperm viability (Daramola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%